If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3y + -7 = -3y + -9 Reorder the terms: -7 + 3y = -3y + -9 Reorder the terms: -7 + 3y = -9 + -3y Solving -7 + 3y = -9 + -3y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '3y' to each side of the equation. -7 + 3y + 3y = -9 + -3y + 3y Combine like terms: 3y + 3y = 6y -7 + 6y = -9 + -3y + 3y Combine like terms: -3y + 3y = 0 -7 + 6y = -9 + 0 -7 + 6y = -9 Add '7' to each side of the equation. -7 + 7 + 6y = -9 + 7 Combine like terms: -7 + 7 = 0 0 + 6y = -9 + 7 6y = -9 + 7 Combine like terms: -9 + 7 = -2 6y = -2 Divide each side by '6'. y = -0.3333333333 Simplifying y = -0.3333333333
| 81x^2+484=8 | | 4(x+3)=7x+15 | | X+7.5=-8 | | 7(3n+7(n+k)+2k)= | | V*2=80 | | 5+5b=2.5b | | y=(c-k)x+1 | | X+7.5=8 | | x^4+2x^2-80=0 | | 6(P+24)=414 | | -2z+4=-27.2+2z | | c=clt | | c=cult | | c=cly | | 5logx=8 | | -81=b-3(7-3b) | | 22=(x-300000)/x | | 7x=-45 | | k=8r-s | | 0.45(6)+0.05x=0.15(12+x) | | 2z+1.1=0+3z | | 120=x+(x-3) | | 10-(2y-4)=7-3y | | 2x^2-242= | | 3m^4+18m^2-120=0 | | 3v+30=-3(v+2) | | 4x^2+20x+106=0 | | (4y^2-5y^3)-(6y^2+5y+7)= | | 2z^2-z-1=0 | | -7y+2(y-7)=1 | | a*25/2=-5/8 | | 4-3(y+2)=16 |